3D graphics rendering cookbook : a comprehensive guide to exploring rendering algorithms in modern OpenGL and Vulkan /: a comprehensive guide to exploring rendering algorithms in modern OpenGL and Vulkan. (2021) - Kosarevsky, Sergey; Latypov, Viktor
No abstract available